Shear bond strength between metal alloy and a ceramic system, submitted to different thermocycling immersion times. - Salazar M, Susana M; Pereira, Sarina M B; Ccahuana V, Vanessa Z; Passos, Sheila P; Vanderlei, Aleska D; Pavanelli, Carlos A; Bottino, Marco A (My University, 2007)
The aim of this study was to evaluate the shear bond strength of Co-Cr and Ni-Cr metal alloys and a specific ceramic, submitted to different thermocycling immersion times. Sixty metal-ceramic specimens were confectioned and standardized in cylindricalformat. Three thermocycling conditions were evaluated: without thermocycling, 3,000 cycles (5 degrees C/55 degrees C+/-1) with 30s of immersion time and 3,000 cycles (5 degrees C/55 degrees C+/-1) with 60s. The shear bond strength was performed in a universal testing machine, using a special device to concentrate the tension at the metal/ceramic interface during the test. The load was applied until fracture of the specimens. The data was statistically analyzed by ANOVA (two-way) and Tukey (p<0.05) test. The results didn't show significant statistic differences between the metal-porcelain combinations. Nevertheless, both metal-ceramic systems submitted to 60s of immersion time showed lower values compared to specimens without thermocycling. It was concluded that the thermocycling immersion time of 1 minute affect the shear bond strength values for the Ni-Cr/porcelain and Cr-Co/porcelain systems.